The Notion of Public Participation in the Making of Government Regulation in Lieu of Law (PERPU) in Indonesia - Al Yasir; Zainal Arifin Mochtar (South East Asian Journal of Advanced Law and Governance (SEAJ-ALGov), 2024)
After the Constitutional Court Decision Number 91/PUU-XVIII 2020, public participation must be present in every legislative formation. As one of the regulations in Indonesia, PERPU has the same hierarchy and content material as the Law. Therefore, it is also important to question the opportunity for public participation in the PERPU formation process. In order to obtain answers to this study, this research uses normative legal research with a statute approach and conceptual approach. This research shows that in the formation of PERPU there are two processes that must be passed, namely first the process of formulating and determining PERPU by the President and second the process of submitting to the DPR for approval or not. Public participation can be present in both processes but has different doses. In the first process, public participation is only in the form of information provided to the public regarding the reasons for the ‘compelling urgency’ of the PERPU stipulation by the President. Meanwhile, in the second process, public participation is presented when the PERPU is submitted and the discussion stage is carried out by the DPR level I and II. As for the implementation of public participation in the formation of PERPU in both processes, it can utilise technology, because PERPU is an emergency regulation and races with time constraints in its formation, technology can be an option used.